Bibliometric analysis of stem cells for spinal cord injury: current status and emerging frontiers - Shang, Zhizhong; Wanyan, Pingping; Wang, Mingchuan; Zhang, Baolin; Cui, Xiaoqian; Wang, Xin (Frontiers in Pharmacology, 2023)
Background: This study aimed to conduct a bibliometric analysis of the literature on stem cell therapy for spinal cord injury to visualize the research status, identify hotspots, and explore the development trends in this field. Methods: We searched the Web of Science Core Collection database using relevant keywords ("stem cells" and "spinal cord injury") and retrieved the published literature between 2000 and 2022. Data such as journal title, author information, institutional affiliation, country, and keywords were extracted. Afterwards, we performed bibliometric analysis of the retrieved data using Bibliometrix, VOSviewer, and CiteSpace. Results: A total of 5375 articles related to stem cell therapy for spinal cord injury were retrieved, and both the annual publication volume and the cumulative publication volume showed an upward trend. NEURAL REGENERATION RESEARCH was the journal with the most publications and the fastest cumulative publication growth (162 articles), Okano Hideyuki was the author with the highest number of publications and citations (114 articles), Sun Yat-sen University was the institution with the highest number of publications (420 articles), and China was the country with the highest number of publications (5357 articles). However, different authors, institutions, and countries need to enhance their cooperation in order to promote the generation of significant academic achievements. Current research in this field has focused on stem cell transplantation, neural regeneration, motor function recovery, exosomes, and tissue engineering. Meanwhile, future research directions are primarily concerned with the molecular mechanisms, safety, clinical trials, exosomes, scaffolds, hydrogels, and inflammatory responses of stem cell therapy for spinal cord injuries. Conclusions: In summary, this study provided a comprehensive analysis of the current research status and frontiers of stem cell therapy for spinal cord injury. The findings provide a foundation for future research and clinical translation efforts of stem cell therapy in this field.